Armageddon or Dabiq - Historical Background to the Tragedy of the Collapse of Syria - Ramos, M. (IITGN Faculty Talk, 21 January 2016, 2016)
The present violent conflict in Syria/Iraq today threatens to reap apart almost a century of status quo in the region, after the fall of the Ottoman empire in the end of WWI. It has been argued that its root causes lie in the two US-led interventions in Iraq, in the 1990s and 2000s, and even before in the carving up of the region by European powers in the 1920s; it has also been argued that the conflict has intensified due to an explosive mix of regional and international foreign inputs. But the complexity of the religious, political and demographic puzzle of the Levant, and the antiquity of the international dimension of Syria/Iraq’s internal dynamics reaches much further down history. The lecture proposes to visit part of that complex history.